A woman in a man's world a descriptive study of the representation of the working Filipino woman in the 10 years of soap operas of ABS-CBN (2000-2010) - Genota, Angelique Velecina 1990- (2012)
"This study addresses the representation of the working Filipino woman in the soap operas produced by ABS-CBN from 2000 to 2010. Using textual analysis, this study examines 17 soap operas having dramatic formats and looks at how they use language and narrative to construct particular images of the working Filipino woman. My theoretical inquiry is how the woman, as an element of a text, undergoes the process of social construction in soap operas. Specifically, how is the working Filipino woman being represented in ABS-CBN soap operas that have been produced from 2000 to 2010? What are the represented professions/occupations of the Filipino woman? I have arrived at 18 professions and 11 images usually depicted of the working Filipino woman. Generally, the images show that the Filipino woman faces gender inequality in Philippine society. This is apparent in how the Filipino woman's prescribed roles as a housewife has become a disadvantage for her in the work force and in her aim for professional and financial success. Moreover, it also shows the inferiority of the Filipino woman to the Filipino man. However, there are also a few images showing the Filipino woman's resistance to the unfair situation with which she is faced."